2007
DOI: 10.1145/1330555.1330570
|View full text |Cite
|
Sign up to set email alerts
|

Product form stationary distributions for diffusion approximations to a flow-level model operating under a proportional fair sharing policy

Abstract: We consider a flow-level model of Internet congestion control introduced by Massoulié and Roberts [2]. We assume that bandwidth is shared amongst elastic documents according to a weighted proportional fair bandwidth sharing policy. With Poisson arrivals and exponentially distributed document sizes, we focus on the heavy traffic regime in which the average load placed on each resource is approximately equal to its capacity. In [1], under a mild local traffic condition, we establish a diffusion approximation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 3 publications
5
9
0
Order By: Relevance
“…This result complements the work of Kang et al [4] who have conjectured the distribution on the number of files in the network in a heavy-traffic regime using Brownian motion models. Assuming there is a single-hop flow on each link (local traffic assumption), it has been shown that…”
Section: Proportionally-fair (Pf)supporting
confidence: 88%
See 4 more Smart Citations
“…This result complements the work of Kang et al [4] who have conjectured the distribution on the number of files in the network in a heavy-traffic regime using Brownian motion models. Assuming there is a single-hop flow on each link (local traffic assumption), it has been shown that…”
Section: Proportionally-fair (Pf)supporting
confidence: 88%
“…Using the Foster-Lyapunov criterion, we derive an upper-bound on the expected number of files in the network under the proportionally-fair policy, and the upper bound increases linearly with the number of flows in the network. This result complements the work of Kang et al [4] who have obtained a conjecture on the distribution on the number of files in the network in a heavy-traffic regime using Brownian motion models. Our upper bound matches the result in [4] in certain symmetric networks.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations